Principles of powder metallurgy - Gill, Pritam Singh (S.K.Kataria and Sons, 2015)
Principles of powder metallurgy / Gill, Pritam Singh. -- New Delhi: S.K.Kataria and Sons, 2015 669 G475 No. of Copies : 1